Usability aspects of distance learning systems and students' response towards distance learning courses - Poh, Eng Wah. (2008)
The purpose of this research is to study the student’s satisfaction towards distance learning. The objective of the first task involves the study of the usability of the distance learning systems, which include the users’ feedback on the system usability after using it. The objective of the second task involves the study of the students’ response towards the distance learning.